The role of entrepreneurial education in determining actual entrepreneurial behavior: Does TESOL amplified communication apprehension matter? - Shen, Jianwen; Huang, Xuebin (Frontiers in Psychology, 2023)
Since the impression of innovation is at the fundamental of commercial standing, therefore, Industries estimate innovation as their competitive advantage. Resultantly, industries devote a lot of resources understanding the versatile and dynamic nature of innovations and also keep on progressing innovation techniques and strategies. To meet the objectives of the study, we collected data from the students studying in Chinese universities. Survey questionnaire was designed to collect data form university students who were part of the TESOL prgaram. A total pf 224 valid questionnaires were used to proceed with the analysis, where, descriptive statistics were calculated using SPSS 21 while hypothesis testing was carried out using Mplus 8. Results revealed the facts that both formal and informal education significantly predicted entrepreneurial behavior, while entrepreneurial intention was also found to mediate the relationship between formal, informal education and entrepreneurial behavior. Similarly, as per prediction, TESOL amplified communication apprehension also significantly moderated the relationships of formal, informal education with entrepreneurial behavior.